Building a Green Industry Based on the Sustainable Development Goals (SDGs) Reports of State-Owned Banks - Mulya Rizki Anugrah, Ce; Wulandari, Rosanna; Zainuddin Hamidi, Dendi (KnE Social Sciences, 2022)
To achieve the Sustainable Development Goals (SDGs) in Indonesia, effort needs to be made by state-owned banks. This study aims to determine the extent to which stateowned banks can support the SDG based on disclosed state-owned banks’ annual sustainability reports. The research aims to identify, within the reports, 17 indicators of Sustainable Development Goals (SDGs) between 2018 and 2021. The study’s results show that state-owned banks have expressed support for the Sustainable Development Goals even though the 17 indicators have not been fully met. Keywords: Banking, Sustainable Development Goals (SDGs), Green Banking